Fast breeder reactor technology and the entrepreneurial state in the UK. Issue 8 (18th October 2022) - MacKenzie, Niall G.; Knox, Stephen; Hannon, Matthew
Abstract: This article explores the creation, operation and failure of the UK's fast breeder reactor programme at Dounreay within the context of the development of the nuclear power industry in the UK, and the administration of national and regional economic policy. The UK government maintained total control of the development of the technology including its creation, operation, and attempts at exploitation, corresponding closely to existing definitions of entrepreneurship. We thus argue that the case of fast breeder reactor technology in the UK should be considered as both an example of Mazzucato's characterisation of the state as an entrepreneur and an explanation why it has 'forgotten' how to be entrepreneurial.